2022
DOI: 10.1186/s12876-022-02280-3
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effectiveness and safety of ustekinumab in bio-naïve and bio-experienced anti-tumor necrosis factor patients with Crohn’s disease: a real-world multicenter Brazilian study

Abstract: Background The effectiveness of ustekinumab (UST) in the treatment of Crohn’s disease (CD) has been demonstrated in the pivotal Phase 3 UNITI 1 and 2 and IM-UNITI studies in both anti-TNF-naïve and anti-TNF-exposed patients. Given the selective nature of pivotal trial designs, real-world effectiveness and safety studies are warranted. We report our experience with UST treatment in a large, real-world multicenter cohort of Brazilian patients with CD. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 39 publications
2
10
0
Order By: Relevance
“…A total of 63 studies (including 8529 patients) met the inclusion criteria and were finally included in the systematic review and meta-analysis ( Figure 1 ) [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , ...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 63 studies (including 8529 patients) met the inclusion criteria and were finally included in the systematic review and meta-analysis ( Figure 1 ) [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , ...…”
Section: Resultsmentioning
confidence: 99%
“…Predictors of response were reported in 37 studies (59%). The most frequent predictors of poor clinical response were previous biologic exposure (anti-TNF and/or vedolizumab) [ 26 , 39 , 40 , 44 , 47 , 51 , 65 , 72 , 74 ], stricturing disease [ 19 , 20 , 39 , 44 , 65 ], penetrating disease [ 27 , 39 , 44 , 51 , 65 ], and high Harvey-Bradshaw index (HBI) at first dose [ 19 , 20 , 51 , 72 , 73 , 75 ]. Concomitant corticosteroids, extraintestinal manifestations, male sex, old age, smoking, and low body mass index were also reported in some studies.…”
Section: Resultsmentioning
confidence: 99%
“…Three real-world studies have reported effectiveness specifically in bio-naïve patients treated with ustekinumab. A study from Brazil by Parra et al 21 reported effectiveness of ustekinumab in 245 patients, most (86.5%) had been previously exposed to biologicals and 33 were bio-naïve. The proportion of bio-naïve patients in clinical remission at weeks 8, 24 and 56 were 36.4%, 54.5% and 39.4%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In CD, the PCDT does not offer any biologic other than anti-TNF drugs. Despite being approved in Brazil, new biologics such as ustekinumab and vedolizumab are not available for these patients [ 28 , 29 ]. Thus, there are no other options for treatment with biologics for patients with primary nonresponse to anti-TNF drugs or with contraindications for anti-TNF use, such as neoplasms, tuberculosis, and congestive heart failure.…”
Section: Discussionmentioning
confidence: 99%